Control of MacPherson active suspension system using sliding mode control with composite nonlinear feedback technique - Ismail, Muhamad Fahezal (2016)
The MacPherson active suspension system is able to support the weight of vehicle and vibration isolation from road profile, and is also able to maintain the traction between tyre and road surface. It also provides both additional stability and maneuverability by performing active roll and pitch control during cornering and braking, and the most significant are ride comfort and road handling performance. However, a drawback of MacPherson model is the self-steer phenomenon in the active suspension system. The problem might be solved by controlling the actuator force and control arm of the system. The MacPherson model has a similar layout to a real vehicle active suspension system. The mathematical model of the system produces a nonlinear mathematical model with uncertainties. Therefore, the proposed control strategy must be able to cater the uncertainties in mathematical model and simultaneously provide a fast response to the system. The control strategy combines Composite Nonlinear Feedback (CNF) algorithm and Proportional Integral Sliding Mode Control (PISMC) algorithm to achieve quick response and to reduce uncertainties. Optimisation of parameters in the CNF was performed using Evolutionary Strategy (ES) algorithm for fast transient performance. Thus, the controller is called Proportional Integral Sliding Mode Control – Evolutionary Strategy – Composite Nonlinear Feedback (PISMC-ES-CNF). To validate the proposed controller, the conventional Sliding Mode Control (SMC) and CNF were utilised to control the system under various road profiles. The ISO 2631-1, 1997 was used as a reference of ride comfort level for the acceleration of sprung mass. Results show that the proposed controller, PISMC-ES-CNF achieved the best control performance under various road profiles. The results obtained also prove that the PISMC-ES-CNF managed to improve ride comfort quality and road handling quality and has also delivered better control performance in terms of transient response of acceleration of sprung mass, reducing overshoot and chattering problem compared to conventional SMC and CNF.